1999
DOI: 10.1073/pnas.96.24.13989
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity and pharmacokinetics of a mixed-backbone antisense oligonucleotide targeted to the RIα subunit of protein kinase A after oral administration

Abstract: Overexpression of the RI␣ subunit of cAMP-dependent protein kinase (PKA) has been demonstrated in various human cancers. PKA has been suggested as a potential target for cancer therapy. The goal of the present study was to evaluate an anti-PKA antisense oligonucleotide (mixed-backbone oligonucleotide) as a therapeutic approach to human cancer treatment. The identified oligonucleotide inhibited the growth of cell lines of human colon cancer (LS174T, DLD-1), leukemia (HL-60), breast cancer (MCF-7, MDA-MB-468), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 43 publications
2
83
0
1
Order By: Relevance
“…In this regard, we found that EGF-related, laterally modi®ed MBOs were very ecient in inhibiting in vivo tumor growth, and did not show any signi®cant toxic eects in nude mice. Laterally modi®ed MBOs have shown bioavailability following oral or rectal administration (Agrawal et al, 1998b;Wang et al, 1999). Preliminary results suggest that oral administration of AR, CR and TGFa MBOs is also able to inhibit GEO tumor growth in nude mice (N Normanno, unpublished observations).…”
Section: Discussionmentioning
confidence: 84%
“…In this regard, we found that EGF-related, laterally modi®ed MBOs were very ecient in inhibiting in vivo tumor growth, and did not show any signi®cant toxic eects in nude mice. Laterally modi®ed MBOs have shown bioavailability following oral or rectal administration (Agrawal et al, 1998b;Wang et al, 1999). Preliminary results suggest that oral administration of AR, CR and TGFa MBOs is also able to inhibit GEO tumor growth in nude mice (N Normanno, unpublished observations).…”
Section: Discussionmentioning
confidence: 84%
“…An improvement of these effects is observed with the MBO GEM 231. This oligo elicits a better in vivo pharmacokinetic and toxicological profile than PS ASOs, and displays antitumor activity in different human tumor xenografts when given orally to mice (Wang et al, 1999).…”
Section: Antisense Oligonucleotides Against Proliferationassociated Tmentioning
confidence: 99%
“…It was demonstrated that treating different tumor cell lines with antisense ODNs targeted against the RI␣ subunit of PKA caused inhibition of cell proliferation in vitro (21,22) and tumor growth in vivo (15,23,24). A single administration of RI␣ antisense to nude mice bearing LS-174T human colon carcinomas resulted in an almost complete suppression of tumor growth for 7 days (15).…”
Section: Introductionmentioning
confidence: 99%